ANALISA RASIO LAPORAN KEUANGAN UNTUK MENGETAHUI KINERJA KEUANGAN PADA PERUSAHAAN ROKOK YANG TERDAFTAR DI BURSA EFEK INDONESIA - Sri Mulyani; Agus Setiawan (SEKOLAH TINGGI ILMU EKONOMI NASIONAL (STIENAS) BANJARMASIN, 2017)
Abstract,This research to determine the financial performance of cigarette companies listed on the Indonesia Stock Exchange. The research method used is quantitative descriptive method, by using financial ratio analysis then elaborated in the form of narration.The results of this study found that PT Wismilak Inti Makmur Tbk has the best liquidity because it is always above 200% for three consecutive years, followed by PT Hanjaya Mandala Sampoerna Tbk, PT Gudang Garam Tbk and PT Bentoel International Investama Tbk. While the good leverage ratio is PT Wismilak Inti Makmur Tbk and PT Gudang Garam Tbk compared to PT Hanjaya Mandala Sampoerna Tbk and PT Bentoel Internasional Investama Tbk. In the ratio of activities that have good activity is PT Hanjaya Mandala Sampoerna Tbk compared with PT Bentoel International Investama Tbk then PT Gudang Garam Tbk and PT Wismilak Inti Makmur Tbk. The best profitability ratio is PT Hanjaya Mandala Sampoerna Tbk, followed by PT Wismilak Inti Makmur Tbk, PT Gudang Garam Tbk and PT Bentoel Internasional Investama Tbk.Conclusion from this research, the company that has the best performance is PT Wismilak Inti Makmur Tbk and PT Hanjaya Mandala Sampoerna Tbk then followed by PT Gudang Garam Tbk and the last is PT Bentoel International Investama Tbk.